Numerical Approach of the Ciliary Muscle Contractrion. A Preliminary Step to Reproduce Human Accommodation - Cabeza Gil, Iulen; Grasa, Jorge; Glasser, A.; Calvo, Begoña (Jornada de Jóvenes Investigadores del I3A, 2020)
Está dentro del documento